MANAGEMENT OF MILD-CHRONIC PSORIASIS WITH THE DEVELOPED CURCUMIN WHEAT OIL-BASED NANOEMULGEL – A CASE STUDY - Javeria Noor-ul-Ain Azdee; Asma Aslam; Kifayat Ullah Khan; Naveed Nisar; Asma mamtaz; Aqsa Afzal; Syed Nisar Hussain Shah (International Journal of Pharmacy & Integrated Health Sciences)
Background: Curcumin and wheat oil are used to reduce psoriasis symptoms by inhibiting inflammation. Objectives: The Case-1 study involved a 41-year-old male who had been grappling with severe psoriatic lesions for several years, while Case-2 centred on a 45-year-old female experiencing mild plaque psoriasis. The objective was to evaluate the therapeutic impact of our curcumin wheat oil-based nanoemulgel (CWOE) in both cases. Methodology: Patients with psoriasis were given a topical curcumin wheat oil-based nanoemulgel twice daily on the affected area. Results: Following the two-month treatment period, notable improvements were observed in the patient's psoriatic lesions, accompanied by a substantial decrease in inflammation. Conclusions: Psoriasis can be effectively treated by applying a wheat oil-based nanoemulgel based on curcumin, which has been shown to be therapeutic in both mild and severe instances. These results imply that CWOE might be an effective treatment for psoriasis symptoms. Additional research could confirm its long-term efficacy and safety.